Role of maximal heart rate and arterial O2 saturation on the decrement of V·O2max in moderate acute hypoxia in trained and untrained men - Mollard, P.; Woorons, X.; Letournel, M.; Cornolo, J.; Lamberto, C.; Beaudry, M.; Richalet, J. P. (International Journal of Sports Medicine, 2007)
We aimed to evaluate 1) the altitude where maximal heart rate (HRmax) decreases significantly in both trained and untrained subjects in moderate acute hypoxia, and 2) if the HRmax decrease could partly explain the drop of V·O2max. Seventeen healthy males, nine trained endurance athletes (TS) and eight untrained individuals (US) were studied. Subjects performed incremental exercise tests at sea level and at 5 simulated altitudes (1000, 1500, 2500, 3500, 4500 meters). Power output (PO), heart rate (HR), arterial oxygen saturation (SaO2), oxygen uptake (V·O2), arterialized blood pH and lactate were measured. Both groups showed a progressive reduction in V·O2max. The decrement in HRmax (Delta HRmax) was significant from 1000 m for TS and 2500 m for US and more important in TS than US (at 1500 m and 3500 m). At maximal exercise, TS had a greater reduction in SaO2 (Delta SaO2) at each altitude. Delta HRmax observed in TS was correlated with Delta SaO2. When the two groups were pooled, simple regressions showed that Delta V·O2max was correlated with both Delta SaO2 and Delta HRmax. However, a multiple regression analysis demonstrated that Delta SaO2 alone may account for Delta V·O2max. Furthermore, in spite of a greater reduction in SaO2 and HRmax in TS, no difference was evidenced in relative Delta V·O2max between groups. Thus, in moderate acute hypoxia, the reduction in SaO2 is the primary factor to explain the drop of V·O2max in trained and untrained subjects.